SELF ASSEMBLY AND MAGNETISM OF LIVING BIOLOGICAL MOLECULES - Sutiman Bambang Sumitro (The East Java Biological Society, 2012)
Biological molecules are essentially nano size structure. All of them are complex structure with specifi c function dedicated to perform normal ordered organizational system. The forces for their work are non-covalent interactions; include spontaneous folding of proteins, DNA, RNA and other bio-macromolecules, ligand-receptors interactions, assembly-disassembly of macromolecule, andtransportation or movement of many other nano size sub cellular components. The non-covalent interactions are weak bonds system that is low energetic chemical and physical forces. The energetic forces are mainly atomic forces such as electromagnetic force emergence from electron spinning and transitions at every atom of the complex macromolecular structure. The energy will work along with different level of energy, and atomic positioning within macromolecules. This paper review and discuss the role of magnetism on molecular working process as part of thermodynamically open systems to develop order, which is constantly receiving, transforming and dissipating energy, can and do continually exhibit self assembly and organization, along with the self repairing, and perpetuation.